Effect of light intensity on survival and photosynthetic efficiency of cultured corals of different ages. (5th April 2020) - Kuanui, Pataporn; Chavanich, Suchana; Viyakarn, Voranop; Omori, Makoto; Fujita, Toshihiko; Lin, Chiahsin
Abstract: In this present study, we investigated the effects of increase and decrease of light intensity and photoperiods on growth, survival, and photosynthetic efficiency in three different corals, Pocillopora damicornis (Linnaeus, 1758), Acropora millepora (Ehrenberg, 1834) and Platygyra sinensis (Milne Edwards and Haime, 1849) with different ages (6-, 12-, and 24-month old). All experimented corals were cultured from sexual propagation. In light intensity trials, juvenile corals were transferred and exposed to different treatments (0, 21, 42, 85, and 169 μmol m −2 s −1 provided by 400-W metal halide lamps or equal to daily light integrals (DLI) of 0, 0.95, 1.89, 3.8, and 7.6 μmol m −2 s −1 ) for 2 weeks, while in the photoperiod experiment, the coral colonies were exposed to 5 different treatments (24/0, 18/6, 12/12, 6/18, and 0/24 h light-and-dark cycle). The results from the light intensity experiment showed that 2-year old Platygyra sinensis survived (100%) under all light intensity levels, while the survival rates of other coral species decreased, ranging between 20 and 80%, when the light intensity levels changed from the ambient light condition. For the photoperiod experiments, the results showed that 2-year old Platygyra sinensis and 1-year old Acropora millepora survived (100%) under all photoperiod levels. However, there was no significant difference on the growth of corals between different light intensity levels and different photoperiods. From this study, Platygyra sinensis seemed to have more tolerance to wider ranges of light intensities and photoperiods than other coral species. In addition, the results implied that corals were able to acclimate to a prolonged light period and light intensity, which can be feasible for future coral aquaculture. Highlights: Light factor on corals remains poorly understood in many coral species with different ages. This study investigated the effect of light intensity and light period on different coral species with different ages. All experimented corals were cultured from sexual propagation technique. The results showed that different ages and different coral species can have different acclimation to the light levels. Corals adapting to wide ranges of light periods and intensities can have more resilience to the environmental changes.